The explanatory power of expenses in the performance of eurozone mutual funds (European Journal of Government and Economics, 2022)
We studied the relationship between the mutual fund’s expenses and their profitability, as well as their ability to predict future performance. We used regressions in panel data with a sample of equity mutual funds of the eurozone area from 2003 to 2014. We concluded that expenses are an important determinant of performance in the eurozone and we show evidence that there is, in the short-term, a negative relationship between the profitability of the year and the level of expenses of the fund. Furthermore, there is also a relationship between the profitability of mutual funds with their level of expenses after one and three years. On the other hand, by applying the quantile regression, it seems clear that the funds with the highest returns have a positive relationship with the level of expenses.